2008
DOI: 10.1016/j.drugalcdep.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and suicide: A brief overview

Abstract: This article provides a brief overview of the rationales, possible mechanisms and epidemiological data on the association of smoking, smoking cessation and cessation medications with suicide. Current smoking is reliably associated with suicide both in case-control and cohort studies. The three most plausible (but relatively untested) explanations for the association are that smokers have pre-existing conditions that increase their risk for suicide, smoking causes painful and debilitating conditions that might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
132
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(155 citation statements)
references
References 82 publications
11
132
2
10
Order By: Relevance
“…The higher frequency of previous suicide attempts among the smokers evaluated in the present study is in line with the fact that current smoking has been reliably associated with suicide, in case-control and cohort studies. 30 The most plausible but relatively untested explanation for that association is that smokers have pre-existing conditions that increase their risk for suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The higher frequency of previous suicide attempts among the smokers evaluated in the present study is in line with the fact that current smoking has been reliably associated with suicide, in case-control and cohort studies. 30 The most plausible but relatively untested explanation for that association is that smokers have pre-existing conditions that increase their risk for suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal smoking exposure may have a long-term influence on offspring serotonin metabolism. Chronic nicotine exposure reduces serotonin metabolism in animals [16], smokers have reduced serotonin levels in the cerebrospinal fluid [17], and reduced serotonin levels is associated with increased risks of suicidal acts [18]. Using a large population-based data set, we studied the association between maternal smoking during pregnancy and risk of completed suicide and suicidal acts in young offspring after taking family history of psychiatric diseases into account.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to its well-known adverse health effects, smoking may also be associated with suicide and suicidal behaviour. 6 The concept of nicotine as a risk factor for suicide is controversial and fuelled by mixed findings across studies. Several studies have found a positive association between smoking and suicide attempts.…”
mentioning
confidence: 99%
“…It also offers the opportunity to examine the relation between smoking cessation and suicidal behaviour, an area with little information and contrasting findings. 6 The primary objective of our study is to determine whether nicotine dependence is associated with suicide attempts. Secondary objectives include investigating the relation between suicide attempts and nicotine cessation, and exploratory analyses of the association with age of first cigarette use, frequency of use, and amount of use.…”
mentioning
confidence: 99%